Factors Influence the Power of EWOM and Consumer’s Purchase Intention: Direct and Indirect Effects - An Empirical Study of Chinese Young People - SHAO, QI (2011)
Background and Purpose -As the development of information technology especially the Web 2.0 technology, nowadays it is possible for people to communicate and share information online and Electronic Word of Mouth (EWOM) becomes an increasingly popular way for people to share and exchange their shopping experience. However, the existing literatures are mainly about the offline WOM. Although some of EWOM literatures can be found, most of them are still follows the traditional WOM theories. Therefore, this study attempts to examine the factors that affect the power of EWOM on influencing consumer’s purchase intention by integrating the information processing model, Lasswell’s ‘5W’ model and technology acceptance model, in addition, some trust theories are also employed to explore the EWOM effects. Specifically, mediating effects of trustworthiness of EWOM between the six independent variables (sender’s expertise, perceived usefulness, perceived ease of use, tie strength, trust propensity and perceived risk) and consumer’s purchase intention will be examined as well as exploring the relationship between the six factors and the mediator (trustworthiness of EWOM) in the context of Chinese young consumer.